Real-Time Non-Invasive Monitoring of Short-Chain Fatty Acids in Exhaled Breath - Meurs, Joris; Sakkoula, Evangelia; Cristescu, Simona M. (Frontiers in Chemistry, 2022)
Short-chain fatty acids (SCFAs) are important metabolites produced by the gut microbiome as a result of the fermentation of non-digestible polysaccharides. The most abundant SCFAs are acetic acid, propionic acid, and butyric acid which make up 95% of this group of metabolites in the gut. Whilst conventional analysis SCFAs is done using either blood or fecal samples, SCFAs can also be detected in exhaled breath using proton transfer reaction- time-of-flight- mass spectrometry (PTR-ToF-MS) using H3O+ for ionization. However, no investigation has been performed to characterize the reactions of SCFAs with H3O+ and with other reagent ions, such as O2+ and NO+. Gas-phase samples of acetic acid, propionic acid, and butyric acid were analyzed with SRI/PTR-ToF-MS under dry and humid conditions. The ions generated and their distribution was determined for each reagent ion. It was found the humidity did not influence the product ion distribution for each SCFA. Using H3O+ as a reagent ion, SRI/PTR-ToF-MS analysis of an exhaled breath sample was performed in real-time to demonstrate the methodology. The presence of SCFAs in exhaled breath was confirmed by thermal desorption – gas chromatography – mass spectrometry (TD-GC-MS). Breath sampling repeatability was within acceptable limits (<15%) for an analytical methodology for each investigated SCFA. Nutritional intervention studies could potentially benefit from real-time monitoring of exhaled SCFAs as an alternative to measuring SCFAs invasively in blood or fecal samples since it is non-invasive, and requires minimal time investment from participants.